Mechanical reinforcement of electrospun poly(vinyl alcohol) by α‐FeOOH nanowires - Šutka, Anna; Järvekülg, Martin; Šutka, Andris; Heinmaa, Ivo; Mäeorg, Uno; Šmits, Krišjānis; Timusk, Martin (Society of Plastics Engineers (SPE), 2018)
We report the mechanical performance of α‐FeOOH nanowire reinforced poly(vinyl alcohol) (PVA) composite nanofiber mat, fabricated using straightforward aqueous processing methods. Goethite (α‐FeOOH) nanocrystals have a high elastic modulus and –OH rich surface, ensuring strong interactions with hydrophilic polymers and effective reinforcement. Needle‐less electrospinning resulted in alignment of the nanowires along fibre axis, as confirmed by transmittance electron microscopy studies. Produced composite PVA nanofibers containing 10 wt% goethite nanoparticles exhibited an outstanding fivefold increase in Young's modulus and 2.5‐fold improvement of tensile strength compared to mats of neat PVA. The addition of α‐FeOOH had a significant influence on glass transition temperature indicating formation of interphase regions around nanowire inclusions. Observed properties are explained by nanowire grafting in the precursor solution, extensive interactions between the adsorbed PVA chains and the matrix and percolation of interphase regions at 10 wt% α‐FeOOH.
The authors kindly acknowledge the financial support of the Estonian Research Council for the post-doctoral research grants of personal research funding in projects PUT1096 and PUTJD578 as well as Institutional Research Funding Projects, IUT20-17, and IUT23-7.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics